Safety and Standards in Edible Packaging: A Framework for Regulatory Alignment and Consumer Protection - , Disha Bongarde, Vaibhav Asane, G.M. Solanke, I.S. Udachan (Archives of Current Research International, 2025)
The review compiles the compositions and the functional properties of biopolymer-based edible packaging materials incorporating active additives. Edible packaging, a sustainable substitute for traditional plastic packaging that has been developed to reduce environmental pollution. However, the efficient use of these advancements has been hampered by concerns about food safety and the lack of a defined framework. It also identifies some of the possible safety hazards of microbial contamination, chemical migration, and allergenicity. The current regulatory regimes around the world are discussed with emphasis on the need for alignment in standards that are meant to protect consumers and ensure product effectiveness. It touches on issues of large-scale production, standards of labelling, and public acceptance as well as advances in nanotechnology and biodegradable sensors. One way forward is creating strategic interventions for the standardization of safety protocols, as well as for promoting sustainable practices, so that edible packaging can be developed and adopted faster, thus aiding environmental conservation and food safety.